Wild Wolves & Wild Women: Awakening a Poetics of Care through the Humanimal - Holmes, Jessica (Journal of Ecohumanism, 2024)
This paper explores the realm of poetry as one space in which to productively contest anthropocentric and patriarchal models of â€œcare.â€ Anchored in the story of the â€œferal wolf-girls,â€ the paper examines the figure of the â€œhumanimalâ€â€”primarily as depicted by Bhanu Kapil in Humanimal: A Project for Future Childrenâ€”through the lens of hybrid rhetoric and ecofeminist poetics. The story of the wolf-girls is at once cultural myth, literary re-telling and archival model; it engages familiar cultural archetypes such as the wild woman/girl, the surrogate mother/father, and the hybrid being or monster, and demonstrates how rhetorical categorizations can both reflect and contribute to hegemonic cultural practices. However, the hybrid figure of the â€œhumanimalâ€ also situates language as a site of negotiation and resistance to normative modes of dominance. By engaging ecofeminist discourses of the body, examining the peripheral borderlands of gender and species categorizations, and drawing parallels to present-day artifices of care, the paper demonstrates how culture upholds standards of conformity and perpetuates patterns of violence toward the vulnerable; and it argues that poetic models such as Kapilâ€™s text carve out a generative space for both intellectual and material resistance.